2015
DOI: 10.1308/003588414x14055925058274
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia rate after laparoscopic colorectal resection is reduced with standardisation of specimen extraction

Abstract: INTRODUCTION Incisional hernia is a common complication of laparoscopic colorectal surgery. Extraction site may influence the rate of incisional hernias. Major risk factors for the development of incisional hernias include age, diabetes, obesity and smoking status. In this study, we investigated the effect of specimen extraction site on incisional hernia rate. METHODS Two cohorts of patients who underwent laparoscopic colorectal resections in a single centre in 2005 (n=85) and 2009 (n=139) were studied retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…However, the comparable incisional hernia rates after LRCS between the two groups in our study was somewhat different from that reported in a systematic review [10], which reported that the incisional hernia rate in midline incision was three times higher than that in transverse incision. Because abdominal wound closure was mostly performed by attending surgeon in our institution, the similar incisional hernia rates in both groups in our study may be explained by the study of Navaratnam et al [27] who reported the incidence of incisional hernia is minimized even in midline incision using the standardized technique. However, some studies [9,28] denoted that midline incision has a higher incisional hernia rate even when using the standardized technique for wound closure during laparoscopic colectomy.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 62%
“…However, the comparable incisional hernia rates after LRCS between the two groups in our study was somewhat different from that reported in a systematic review [10], which reported that the incisional hernia rate in midline incision was three times higher than that in transverse incision. Because abdominal wound closure was mostly performed by attending surgeon in our institution, the similar incisional hernia rates in both groups in our study may be explained by the study of Navaratnam et al [27] who reported the incidence of incisional hernia is minimized even in midline incision using the standardized technique. However, some studies [9,28] denoted that midline incision has a higher incisional hernia rate even when using the standardized technique for wound closure during laparoscopic colectomy.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 62%
“…This approach is associated with increased rates of IH compared to off-midline extractions sites, such as a Pfannenstiel incision. [9, 14, 17, 18] In our study, only 10% of R-RC and only 1 L-RC case were performed with alternative incisions and there were no IH in Pfannenstiel incisions. In addition, all Pfannenstiel incisions and the majority of other non-midline incisions were performed in the 11 patients undergoing intracorporeal anastomoses.…”
Section: Discussionmentioning
confidence: 52%
“…In a 2008 Cochrane review, only 2 trials reported IH rates after laparoscopic colectomy, and with significantly different results (4.7 and 23%). [1114] Data regarding the IH rate after robotic colectomy are even sparser. In a recent meta-analysis of 6 R-RC versus L-RC trials, only 3 studies reported the IH rate; in a total of 70 R-RC patients, the IH rate was 1%.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was further compounded by a study analysing ICA vs ECA following right colectomy in obese patients displaying a significant increase in incisional hernia rate in the ECA group. A study examining the standardization of specimen extraction in laparoscopic colorectal surgery reported an incisional hernia rate of 15.3% in patients with a transverse muscle splitting incision . Moreover, the authors reported an early return to gut function in patients with ICA.…”
Section: Discussionmentioning
confidence: 99%